Costurando o fio da memória: a trajetória de Rosalina Santos, costureira negra na “Aracaju romântica” (1924-2021) - Gomes, José Edwyn Silva (2023)
In the sands of “Romantic Aracaju of the 1940s and 1950s” stories of black women and men unfolded, real plots were played out by these subjects until then “excluded from history”. We present an analysis of the life trajectory of Rosalina Santos, a seamstress for the white “madams” in the capital, granddaughter of former slaves. Rosalina Santos was born in Divina Pastora/SE in 1924 and stood out as a seamstress or “fashionist” of the so-called “high society of Aracaju”. We present aspects of her daily life, identifying in her memories the importance of the family, especially her godmother in her upbringing, the permanence of the slave mentality and the racism present in labor relations. What were the effects of everyday racism on her trajectory? How was it possible to become a seamstress for this clientele? What were the working conditions for black women in that period? What were your strategies? Finally, what was left of Africa in her memories?